Modeling and Computation of CO2 Allowance Derivatives Under Jump-Diffusion Processes (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we study carbon emission trading whose market is gaining popularity as a policy instrument for global climate change. The mathematical modelis presented for pricing options on $CO_2$ emission allowance futures with jump diffusionprocesses, and a so-called fitted finite volume method is proposed to solve thepricing model for the spatial discretization, in which the Crank-Nicolson is employedfor time stepping. In addition, the stability and the convergence of the fully discretescheme are given, and some numerical results, which are compared with the closedform solution and the Monte Carlo simulation solution, are provided to demonstratethe rates of convergence and the robustness of the numerical method.